Energy Implications of Thermal Comfort in Buildings considering Climate Change (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The Special Issue, entitled "Energy Implications of Thermal Comfort in Buildings considering Climate Change", addresses the critical nexus between energy efficiency and thermal comfort in buildings, particularly in the context of global climate change. This compilation presents cutting-edge research and innovative strategies aimed at optimizing indoor environments to enhance occupant comfort while minimizing energy consumption. Topics include thermal comfort models, passive and active design strategies, energy-efficient HVAC systems, and the role of renewable energy sources in maintaining thermal comfort. By integrating multidisciplinary approaches, this Special Issue provides valuable insights for architects, engineers, policymakers, and researchers focused on creating sustainable and resilient built environments in the face of evolving climatic conditions.